Equitable Mindfulness: A Framework for Transformative Conversations in Higher Education - Cash, Tiara A.; Gueci, Nika; Pipe, Teri (Building Healthy Academic Communities Journal, 2021)
Background: Mindfulness, the practice of present moment experience, can be employed as a tool for grounding in difficult conversations and creating pathways for transformative change in communities. Aim: As educators continue to teach the practices of mindfulness in primary, secondary, and post-secondary institutions to promote personal and academic wellbeing, it is important to recognize the inherent power of mindfulness practice to stimulate actions against oppressive systems, instead of continuing to support them by using curriculum focused on desensitizing individuals to that system. The outlined framework aims to create a platform for the promotion of sustained action. Methods: This article will outline the framework and model of Equitable Mindfulness used within curricula to create containers, hold space, and begin difficult conversations about creating and sustaining diverse and inclusive spaces and strategies. Results: Rooted in the foundations of mindfulness, the Equitable Mindfulness framework was created to promote personal and societal introspection while bridging gaps between communities and breaking down barriers against inclusive practices. Conclusions: Researchers are continuing to collect mixed-methods data on how Equitable Mindfulness is perceived, it’s validity in the field, and its relationship to mediating difficult topics.